A modular design approach for PEM electrolyser systems with homogeneous operation conditions and highly efficient heat management. (6th January 2020) - Wirkert, F.J.; Roth, J.; Jagalski, S.; Neuhaus, P.; Rost, U.; Brodmann, M.
Abstract: Because of its advantages, which are fast response times, high power densities and, therefore, compact system design, using polymer electrolyte membrane electrolyser (PEMEL) technology is a promising way to store the excess energy generated by renewable energy sources. With the approach of hydraulic cell compression homogeneous pressure and current distribution is guaranteed, and waste heat management as well as high-pressure operation are improved compared to conventional mechanically compressed PEMEL stacks. The new design approach presented in this work brings the concept of hydraulic cell compression close to an industrial design while preserving the mentioned advantages and providing a high level of modularity. The concept was experimentally validated for hydrogen production using a laboratory scale stack consisting of five single cells having an active cell area of 25 cm 2 each. A study on process water independent stack temperature control was performed using water as a hydraulic medium. Furthermore, the capability of high-pressure operation was investigated up to a process media pressure of 30 bar. Highlights: Hydraulic cell compression improves polymer electrolyte membrane electrolysis. Cell compression is homogeneous independent of size and number of cells per stack. Process water independent temperature management increases system efficiency. Optimal cell compression is guaranteed at any gas output pressure. Modularity on cell level makes the system layout completely customizable.